The Optimum Solution of Quadratic programming problem By Wolfe’s using two –phase Simplex method - Elmahdi, Nafisa Abdalmaged Ali; Hashim, Mohsin Hassan Abdallah; yousif, Osman Omer Osman; Mohammed Adam, Fatima Awed (Gezira Journal of Engineering and Applied Sciences; Vol 17 No 2 (2022), 2026)
Quadratic programming (QP) solves the problem of maximizing a quadratic objective function subject to linear constraints. An alternative approach to Wolfe's method for Quadratic Programming problem (QPP) is proposed. It is a two –phase simplex method This method is simple to use when dealing with non-linear programming problems (NLPP) such as QPP. We developed a new strategy for solving a QPP using Wolfe's two –phase simplex method, which is based on an iterative procedure. When the new strategy is compared to the original Wolfe's two –phase simplex method in sense of computational process for solving NLPP, we found that the new method requires less or at most the same amount of iterations as Wolfe's two –phase simplex method. We discovered that the rule of selecting a pivot vector at the beginning of the process required more iterations for various NLPPs to achieve optimality. We choose the pivot vector in the first stage using the new rules mentioned. The technique yielded the best result after few iterations. The method produces efficient results. تُستخدم البرمجة التربيعية لحل مسائل  تعظيم دالة هدف تربيعية تخضع لقيود خطية. نقترح حلاً بديلاً لطريقة وولف لحل مسائل البرمجة التربيعية ، وهو طريقة سيمبلكس ثنائية المراحل. تتميز هذه الطريقة بسهولة استخدامها عند التعامل مع مسائل البرمجة غير الخطية مثل مسائل البرمجة التربيعية. طورنا استراتيجية جديدة لحل مسائل البرمجة التربيعية باستخدام طريقة وولف سيمبلكس ثنائية المراحل، والتي تعتمد على إجراء تكراري. عند مقارنة الاستراتيجية الجديدة بطريقة وولف الأصلية من حيث العملية الحسابية لحل مسائل البرمجة غير الخطية، وجدنا أن الطريقة الجديدة تتطلب عددًا أقل من التكرارات، أو على الأكثر نفس عدد التكرارات. وجدنا أن مبدأ اختيار متجه محوري في بداية الإجراء يتطلب عددًا أكبر من التكرارات لمختلف مسائل البرمجة غير الخطية للوصول إلى الحل الأمثل. نختار المتجه المحوري في المرحلة الأولى باستخدام القواعد الجديدة المذكورة. حققت هذه التقنية أفضل النتائج بعد بضع محاولات. وتُنتج هذه الطريقة نتائج فعّالة.